2021
DOI: 10.1002/jha2.195
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital mortality in SARS‐CoV‐2 stratified by hemoglobin levels: A retrospective study

Abstract: This study is to estimate in‐hospital mortality in severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) patients stratified by hemoglobin (Hb) level. Patients were stratified according to hemoglobin level into two groups, that is, Hb <100 g/L and Hb >100 g/L. A total of 6931 patients were included. Of these, 6377 (92%) patients had hemoglobin levels >100 g/L. The mean age was 44 ± 17 years, and 66% of the patients were males. The median length of overall hospital stay was 13 days [2; 31]. The remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
(30 reference statements)
3
10
0
Order By: Relevance
“…More importantly, SARS-CoV-2 infected patients with anemia had an approximately 70% higher risk of death in the short-term period compared to those without. Our findings are in accordance with the results presented by Al-Jarallah et al who reported that COVID-19 patients having a hemoglobin > 10 g/dL had lower odds of dying than those who were considered anemic (i.e., Hb < 10 g/dL) (aOR: 0.33, 95% CI: 0.20 to 0.55, p < 0.001) [ 16 ]. However, considering that these authors used in their multivariate analysis those patients without anemia as a reference group, we excluded this investigation from global risk estimation in our meta-analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More importantly, SARS-CoV-2 infected patients with anemia had an approximately 70% higher risk of death in the short-term period compared to those without. Our findings are in accordance with the results presented by Al-Jarallah et al who reported that COVID-19 patients having a hemoglobin > 10 g/dL had lower odds of dying than those who were considered anemic (i.e., Hb < 10 g/dL) (aOR: 0.33, 95% CI: 0.20 to 0.55, p < 0.001) [ 16 ]. However, considering that these authors used in their multivariate analysis those patients without anemia as a reference group, we excluded this investigation from global risk estimation in our meta-analysis.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 2527 articles were obtained by our search strategy. After excluding duplicates and preliminary screening, 1243 full-text articles were assessed for eligibility and 984 studies were excluded for not meeting the inclusion criteria while 254 for unavailable outcome, leaving 5 investigations fulfilling the inclusion criteria [ 6 , 7 , 16 , 17 , 18 ]. A flow diagram of the literature search and related screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to risk factors for COVID-19 related severity, the only variable that held up to MVA for the outcome of hospitalization was admission Hb; this is consistent with previous findings of a significant Hb decrease from baseline for SCD patients requiring hospitalization [1] and studies that reported Hb as a strong predictor of COVID-19 related severity or mortality in the general population [16] , [24] , [25] For the outcome of ICU admission, 3 variables remained significant in the MVA: HCW employment, HU use, and immature granulocyte count on admission. HCW employment has not been previously reported as a risk factor in SCD ICU admission but has been associated with COVID-19 morbidity in the general US population as well as comprehensive meta-analysis [13] , [14] .. HU use has been reported to reduce morbidity in SCD in one report [1] but not others [10] , [21] .…”
Section: Discussionsupporting
confidence: 87%
“…Multiple studies have addressed clinical outcomes in COVID-19 patients: many of them have shown a correlation of mortality with advanced age and male gender; some have shown an association with smoking and certain chronic comorbidities, such as underlying diabetes mellitus, chronic renal insufficiency, chronic obstructive lung disease, and cardiovascular diseases; some have addressed clinical parameters, such as the severity of respiratory failure [ 8 ] and acute renal failure; and others have addressed laboratory investigations as predictors of outcome and found significant correlations with certain inflammatory markers, such as high-sensitivity C-reactive protein, D dimer, and procalcitonin [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%